Impaired cognitive and motor function are coincident with l-DOPA-induced dyskinesia in a model of Parkinson’s disease - Mariah J. Lelos; Ellen M. Murphy; Hanna S. Lindgren; Stephen B. Dunnett; Emma L. Lane (Scientific Reports, 2023)
Abstract Dopamine transmission has been implicated in motor and cognitive function. In Parkinson’s disease (PD), dopamine replacement using the precursor drug l-DOPA is the predominant treatment approach, but long-term exposure leads to the onset of dyskinesias (LIDs). Chronic l-DOPA exposure has been associated with changes in gene expression and altered cortico-striatal plasticity. The aim of this research was to assess the functional consequence of long-term l-DOPA exposure on cognitive and motor function using a rodent model of PD. Across two independent experiments, we assessed the impact of chronic l-DOPA exposure, or a control D2R agonist, on motor and cognitive function in intact and in hemi parkinsonian rats, in the absence of drug. Abnormal involuntary movements associated with LID were measured and brain tissues were subsequently harvested for immunohistochemical analysis. Exposure to chronic l-DOPA, but not the D2R agonist, impaired motor and cognitive function, when animals were tested in the absence of drug. A meta-analysis of the two experiments allowed further dissociation of l-DOPA -treated rats into those that developed LIDs (dyskinetic) and those that did not develop LIDs (non-dyskinetic). This analysis revealed impaired cognitive and motor performance were evident only in dyskinetic, but not in non-dyskinetic, rats. These data reveal a functional consequence of the altered plasticity associated with LID onset and have implications for understanding symptom progression in the clinic.